Simultaneous degradation of the anticancer drugs 5-fluorouracil and cyclophosphamide using a heterogeneous photo-Fenton process based on copper-containing magnetites (Fe3-xCuxO4) - Emídio, Elissandro Soares [UNESP]; Hammer, Peter [UNESP]; Nogueira, Raquel F. Pupo [UNESP] (Elsevier, 2020)
The effect of substitution of iron by copper in the magnetite lattice was investigated in terms of the catalytic activity in the heterogeneous photo-Fenton process. The physicochemical properties of the Fe3-xCuxO4 nanoparticles were characterized by X-ray diffraction (XRD), X-ray fluorescence (WD-XRF), specific surface area measurements, field emission scanning electron microscopy (FEG-SEM), and X-ray photoelectron spectroscopy (XPS). Copper-modified magnetite showed higher catalytic activity for H2O2 conversion to HO• (estimated using 7-hydroxycoumarin), compared to pristine magnetite (Fe3O4). Consequently, improved degradation of the anticancer drugs 5-fluorouracil (5-FU) and cyclophosphamide (CP) was observed, with high efficiencies achieved using Fe2.75Cu0.25O4 (0.125 g L−1) and 15 mmol L−1 H2O2, at pH 6.5, which resulted in complete degradation of 7.7 μmol L−1 5-FU and CP after 150 min. Low leaching of Cu and Fe demonstrated the stability of the catalyst in the Fenton process, with high catalytic activity (>90%) maintained after use in 4 cycles. The addition of radical scavengers such as methanol, tert-butanol and iodide ions indicated that surface-bonded hydroxyl radicals played a major role in the degradation of 5-FU and CP in the Fe3-xCuxO4/H2O2 system. The substitution of octahedral Fe(II) sites of the magnetite lattice by Cu(II) and the partial oxidation of Cu(I) to Cu(II) and Fe(II) to Fe(III) on the catalyst surface after the Fenton reaction were confirmed by analysis of the XPS spectra.
Keywords: Cu modified nanoparticles; Cytostatic drugs; Fenton reaction; Hydroxyl radicals; Magnetite